Comparing functional efficacy of transforaminal vs interlaminar epidural steroid injection for lumbar disc disease!! Do we really need transforaminal epidural route injections? - Eman M P. Gharu; Noel S Singh; Rajesh Paul; Narjeet K Osahan (Wolters Kluwer Medknow Publications, 2024)
This study compared the functional efficacy of therapeutic transforaminal versus interlaminar epidural steroid injection. Adult patients were selected and randomized using an online research randomizer website and assigned into two groups and were given epidural injection either via transforaminal route or interlaminar route. The outcome was measured based on the Modified Japanese Orthopedic Association back index score (mJOA), Oswestry disability index (ODI), and visual analog scale (VAS) over a follow-up on 1st, 3rd, and 6th month postinjection period. It was found that there was no significant difference seen in m JOA, ODI, and VAS score at 1 month, 3 months, and 6 months between transforaminal and interlaminar epidural steroid injection. Pain management in the epidural route was comparable to the interlaminar route. Even though the transforaminal epidural route has the advantage of being a selective nerve route block, it has similar results as the interlaminar route at 6 months follow-up.